Multilayered siRNA nanoparticles as a delivery system for extended gene silencing effect - Ng, Alice Jie Ying (Nanyang Technological University, 2020)
At present, various diseases occur without an effective mode of treatment. The production of undesirable proteins leads to the onset of many diseases. For instance, an elevated expression of secreted protein acidic and rich in cysteine (SPARC) is linked with fibrosis and the inhibition of SPARC expression reduces fibrosis. This work reports on the successful development of an optimized multilayered nanoparticles (NPs) system, utilizing fibrosis as a model to evaluate the effectiveness of the system in releasing siRNA within cell cytoplasm and the suppression of protein production over 3 weeks. The significance of utilizing the layer by layer (LbL) system is to protect the siRNA from degradation by cellular enzymes and to increase its cell internalization property. The multilayered NPs system contains hydroxyapatite (HAp) NPs as the core material, with alternating layers of the cationic polyelectrolyte poly-L-arginine (PLR) and the SPARC siRNA. The 7 layered LbL NPs coated with PLR >70 000 Da and loaded with 3 layers of siRNA demonstrated the highest total siRNA content compared to other prototypes (lower PLR Mw and lesser siRNA layers) and it was employed for the subsequent in vitro tests. The 7 layered LbL NPs of HAp | PLR | siRNA | PLR | siRNA | PLR | siRNA | PLR configuration was 431.30 nm in hydrodynamic diameter with positive surface charge of 42.13 mV. The in vitro study showed that the NPs treatment did not cause toxic effects to the Human retroperitoneal fibroblast (HuRPF) cells. The qualitative and quantitative cellular internalization of LbL NPs showed the presence of 6FAM GFP-labelled NPs in HuRPF cells over 21 days. Further, the 7L LbL NPs ability to escape from the endosome to release siRNA in the cytoplasm (site of action of siRNA) was investigated. The amount of free siRNA within HuRPF cells and the SPARC knockdown study were evaluated over 21 days. It is important to note that the siRNA was present within the cells and was able to elicit a significant SPARC knockdown activity over 21 days. Moreover, the siRNA release profile (within the cells and in PBS medium) showed similar release behavior over 21 days. This suggests the disassembly of LbL NPs through a layer by layer ‘onion effect’ (starting with the outermost layer) leading to the constant release of siRNA in the cell cytoplasm. This is the first time a study was done to investigate the multilayered delivery system releasing siRNA within the cells/cytoplasm to cause an effective and prolonged gene silencing effect over 3 weeks with just a single application.